Hypertension Education and Complementary Therapy Using Pineapple Peel Extract Balm to Support Blood Pressure Control in the Elderly - Palupi, Eva Riantika Ratna; Pamungkas, Indra Gilang; Kusuma, M. Iqbal Angga; Handayani, Fitri; Bunga, Dinda Nur Fajri Hidayati; Suprayogi, Suprayogi; Khoirot, Risyda Ma'rifatul; Sabiha, Febinda Azra (Universitas Malahayati Lampung, 2026)
ABSTRACT Hypertension remains one of the most prevalent non-communicable diseases globally and in Indonesia. Interventions such as education combined with complementary therapies utilizing local wisdom (pineapple peel extract) have not been widely implemented, making them necessary to address the problem of hypertension in patients. This community service project aims to implement health education and the use of complementary therapies to support hypertension management in the community. Community service was conducted using health education methods combined with complementary therapy training based on local wisdom (pineapple peel extract balm) in Kalijati District, Subang. The education was provided for one day, while the pineapple peel extract balm was applied for seven days. Knowledge scores were measured before and after the health education, while blood pressure measurements were taken before and after the pineapple peel extract balm application. The results showed that there were positive changes in the knowledge of hypertension patients from 4.775 to 6.825 (Mean Difference: 2.05), systolic blood pressure from 145.15 to 143.25 (Mean Difference: 1.9), and diastolic pressure from 87.5 to 85.9 (Mean Difference: 1.6). This community service activity increases patient knowledge regarding hypertension and reduces both systolic and diastolic blood pressure. Keywords: Blood Pressure Management, Complementary and Alternative Medicine, Health Education, Hypertension, Pineapple Peel Extract Balm.